EFEKTIVITAS EDUKASI MANAJEMEN CAIRAN TERHADAP NILAI INTERDIALYTIC WEIGHT GAIN (IDWG) PASIEN DENGAN HEMODIALISIS : A LITERATURE REVIEW - Dwi Kurniawati (2020)
Hemodialysis is the most commonly used kidney replacement therapy in patients which suffering from Chronic Kidney Disease (CKD). In hemodialysis therapy, the function of the kidneys in cleaning and regulating blood plasma levels is replaced by machines. The main problem that generally occurs in patients undergoing hemodialysis therapy is weight gain between two hemodialysis times or called Interdialytic Weight Gain (IDWG). Interdialytic Weight Gain (IDWG) is an increase in fluid volume which characterized by an increase in body weight as an indicator to determine the amount of fluid entering during the interdialitic period and patient compliance with fluid management. This study aims to examine existing research to determine accurate evidence related to the effectiveness of fluid management education on the value of Interdialytic Weight Gain (IDWG) patients with hemodialysis. Research using the Literature Review study method by searching the literature using electronic database as PubMed and Google Scholar regard by the inclusion criteria which is the article should have a full-text access, discussing about the effectiveness of fluid management education on the value of Interdialytic Weight Gain (IDWG) patients with hemodialysis in the last 5 years of publication. Based on literature review in 6 research journals, significant results were obtained between the education provided and the change in Interdialytic Weight Gain (IDWG) values of patients (p <0.05).